DIALECTIC RELATIONSHIP BETWEEN THE QUR’AN AND HADITH: THE INTERPRETATION OF THE TERM “AS-SĀ‘AH” USING CRITICAL HERMENEUTIC ANALYSIS - Amir, Abdul Muiz; Syamsuddin, Sahiron; Masruri, Siswanto (Jurnal Adabiyah, 2021)
This study aims to uncover the polemic relationship between the Qur’an and the Hadith regarding the concept of as-sā‘ah (the end of life in the world). This phenomenon was investigated using a philosophical analysis-based qualitative research design. This study uses critical hermeneutic reading to textualize and historically contextualize the articulations of the as-sā‘ah in the al-Qur’an and Hadith. The findings suggest that the polemic was sparked by a disagreement between the al-Qur’an and Hadith narrations over the meaning of as-sā‘ah. The Qur’an only mentions it in the context of eschatology, whereas some Hadith narrations include descriptions of the end times or events that occur before the Day of Judgment (apocalyptic). The impact of meaning evolution is felt not only on a conceptual level but also on a practical level. Eschatology is limited to conveying spiritual morality messages, whereas apocalyptic is more commonly used for political propaganda that is prone to instilling violent ideas in religion. This finding has ramifications for the study of the Qur’an and Hadith, particularly in the area of examining the text and historical contexts to comprehend the relationship between the Qur’an and Hadith narrations.Keywords: As-Sā‘ah; Critical Hermeneutics; The Qur’an and Hadith.الملخصأهداف هذه الدراسة الكشف عن العلاقة بين نصوص القرآن والحديث في قضية ”الساعة“ التي تؤدّي إلى الجدل. تمت دراسة هذه القضية باستخدام المنهج النوعي بناء على التحليل الفلسفي. وهذا التحليل يبنى على التأويلية النقدية لكلمة ”الساعة“ الواردة في نصوص القرآن والحديث حرفيا وسياقيا تاريخيا. تشير نتائج هذه المقالة إلى أن الجدل في معاني "الساعة" يبدو بسبب اختلاف معانيها في القرآن والأحاديث النبوية. اقتصر القرآن على توضيح معاني ”الساعة“ في سياق الإيمان بالآخرة فحسب، بينما يوضح بعض روايات الحديث ”الساعة“ في سياق الرؤيا أو الحوادث التي جاءت قبل وقوع الساعة أيضا. إن تأثير التحول في المعانى لا يقف في الجانب المفاهيمي ، ولكن يؤثر أيضا في الجانب التطبيقي. مفهوم ”الساعة“ في القرآن لإيصال التعاليم في المجالات الأخلاقية والروحية، بينما يتم استخدام مفهوم ”الساعة“ في الأحاديث بشكل أكثر للدعاية في قضايا السياسية التي تميل إلى ظهور مفاهيم العنف في التدين. ونتيجة هذه الدراسة لها إسهام في تطور دراسة القرآن والحديث خاصة في معرفة جدلية البحث النصي والتاريخي بين نصوص القرآن ورواية الحديث.الكلمات الدلة: الساعة; التأويلية النقدية; القرآن والسنة.ABSTRAKStudi ini bertujuan untuk mengungkap relasional antara al-Qur’an dan Hadis terkait konsep akhir kehidupan di dunia (as-sā‘ah) yang tampaknya bersifat polemik. Fenomena tersebut diinvestigasi dengan menggunakan desain penelitian kualitatif berbasis analisis filosofis. Analisis ini menerapkan pembacaan hermeneutika kritis terhadap artikulasi as-sā‘ah yang terdapat dalam redaksi al-Qur’an dan Hadith, baik secara tekstual maupun kontekstual historis. Hasil temuan menunjukkan bahwa polemik tersebut diakibatkan karena terjadinya kesenjangan makna as-sā’ah antara redaksi al-Qur’an dan Hadis. Al-Qur’an hanya sebatas mengartikulasikannya dalam konteks eskatologi, sedangkan sebagian riwayat Hadis juga mencakup deskripsi akhir zaman atau peristiwa yang mendahului hari Kiamat (apokaliptik). Dampak dari evolusi makna tersebut tidak hanya terjadi pada aspek konseptual, tetapi juga pada aspek praksisnya. Eskatologi sebatas digunakan untuk menyampaikan pesan-pesan moralitas spiritual, sedangkan apokaliptik lebih dominan digunakan untuk propaganda politik yang rentan menimbulkan paham kekerasan dalam beragama. Temuan ini berimplikasi kepada pengembangan studi al-Qur’an dan Hadis, khususnya pada wilayah investigasi teks dan konteks historis dalam memahami relasional antara redaksi al-Qur’an dan riwayat Hadis.